Improved HaloTag Ligand Enables BRET Imaging With NanoLuc - Thirukkumaran, Ovia Margaret; Wang, Congrong; Asouzu, Nnamdi Joseph; Fron, Eduard; Rocha, Susana; Hofkens, Johan; Lavis, Luke D.; Mizuno, Hideaki (Frontiers in Chemistry, 2020)
Bioluminescence resonance energy transfer (BRET) from an exceptionally bright luciferase, NanoLuc, to a fluorescent HaloTag ligand is gaining momentum to monitor molecular interactions. The recommended use of HaloTag618 ligand for the NanoLuc-HaloTag BRET pair is versatile for ensemble experiments due to their well-separated emission bands. However, this system is not applicable for single-cell BRET imaging because of its low BRET efficiency and in turn weak acceptor signals. Here we explored the unprecedented potential of rhodamine based HaloTag ligands, containing azetidine rings, as BRET acceptors. Through a comprehensive evaluation of various commercial and Janelia Fluor HaloTag ligands for improved BRET efficiency and minimal donor signal bleed-through, we identified JF525 to be the best acceptor for microscopic BRET imaging. We successfully employed BRET imaging with JF525 to monitor the interaction of protein kinase A catalytic and regulatory subunit. Single-cell BRET imaging with HaloTag JF525 can henceforth open doors to comprehend and interpret molecular interactions.